HORNER SYNDROME DUE TO TRAUMATIC CLAVICLE FRACTURE - Guerra, Marta (2017)
Objective: Describe a unique case of preganglionic Horner Syndrome due to middle third clavicle fracture. Methods: A 40 year-old man, hemodynamically stable, presented at the emergency room with left ptosis and miosis after a car accident. Complete ophthalmological examination including external exam, pupil and extraocular movement evaluation, best corrected visual acuity, biomicroscopy, tonometry and fundus exam was performed. Further investigation included chest and pelvic X-rays and pharmacological testing of pupillary reactions. Results: Ophthalmological examination showed no alterations except for ptosis and miosis on the left eye. The X-rays revealed displaced clavicle fracture, third rib and ischiopubic branch fractures on the left side. Apraclonidine and phenylephrine tests diagnosed second-order sympathetic chain lesion. One year later, ptosis persisted and conjunctivo-müllerectomy was performed. Conclusion: Traumatic mild ptosis and miosis alert to sympathetic chain interruption. Pharmacological tests are essential to localize and identify its cause. We present a preganglionic Horner Syndrome due to isolated middle third clavicle fracture, which to our knowledge is reported for the first time.